Les réseaux de distribution des voyages aux États-Unis - Sheldon, Pauline (Téoros, 1990)
The U.S. Travel distribution network is changing as less traditional intermediaries and more advanced technologies are developed to match suppliers with consumers. Computer networks are likely to become more global, more comprehensive and more accessible to all travel planners making their jobs easier. All travel planners will be presented with new challenges and demands as the travel market diversifies. The nature of the travel product will ensure the existence of travel intermediaries, however, their future success will be dependent on their ability to adapt to change.